Chironomidae from Gough, Nightingale and Tristan da Cunha islands - Sæther, Ole A.; Andersen, Trond (Zootaxa, 2011)
The resurrection of trans-oceanic dispersal is the most striking aspect of a major shift in historical biogeography toward a more even balance between vicariance and dispersal explanations. Molecular dating of lineage divergences favors oceanic dispersal over tectonic vicariance as an explanation for disjunct distributions in a wide variety of taxa. Although many oceanic islands harbor a disproportionately high biodiversity and number of endemic taxa, the chironomid fauna of the South Atlantic islands of Gough, Nightingale and Tristan da Cunha apparently consists of 6 species only: Telmatogeton goughi sp. n. (described as male and female), Limnophyes minimus (Meigen), Smittia sp. (described as female), Thalassosmittia christinae sp. n. (described as female), Clunio jonesi sp. n. (described as male) and Allocladius lusciniolus Sæther et Andersen (described as female). Except for the marine T. goughi and C. jonesi the other species are parthenogenetic. Limnophyes minimus and A. lusciniolus dominate the chironomid fauna. Telmatogeton goughi is close to T. sanctipauli (Schiner). Thalassosmittia christinae differs from T. thalassophila (Bequaert et Goetghebuer) by having hairy eyes and antenna with subapical seta. Clunio jonesi differs from C. africanus and C. gerlachi by having ultimate flagellomere as long as the 4 preceding segments and gonostylus with only 1–2 apical spines. Allocladius lusciniolus differs from other known females of the genus by having 1–5 setae apically on M 1+2 .